2018
DOI: 10.1292/jvms.17-0641
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin deficiency-induced diabetes increases TNFα and FFA via downregulation of PPARα

Abstract: Expression of peroxisome proliferator-activated receptor (PPAR) α was investigated in adiponectin knockout mice to elucidate the relationship between PPARα and adiponectin deficiency-induced diabetes. Adiponectin knockout (Adp−/−) mice were generated by gene targeting. Glucose tolerance test (GTT), insulin tolerance test (ITT), and organ sampling were performed in Adp−/− mice at the age of 10 weeks. PPARα, insulin, triglyceride, free fatty acid (FFA), and tumor necrosis factor α (TNFα) were analyzed from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The oxidative stress (MDA and protein carbonyl groups) and inflammatory (TNF‐α, IL‐1β, and IL‐6) markers also augmented, while the antioxidant (GSH, GPx1, GR, and CAT) and anti‐inflammatory (IL‐10) molecules declined, in the PC than the NC hepatic tissues. Our data are aligned and support the “multiple‐hit” theory, which proclaims that MAFLD pathogenesis involves complex interactions between insulin resistance, distorted lipid metabolism, dysregulation of adipokines, oxidative stress, and chronic inflammation 3–18 …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The oxidative stress (MDA and protein carbonyl groups) and inflammatory (TNF‐α, IL‐1β, and IL‐6) markers also augmented, while the antioxidant (GSH, GPx1, GR, and CAT) and anti‐inflammatory (IL‐10) molecules declined, in the PC than the NC hepatic tissues. Our data are aligned and support the “multiple‐hit” theory, which proclaims that MAFLD pathogenesis involves complex interactions between insulin resistance, distorted lipid metabolism, dysregulation of adipokines, oxidative stress, and chronic inflammation 3–18 …”
Section: Discussionsupporting
confidence: 71%
“…12,13 However, MAFLD is commonly linked with hyperleptinemia alongside declines in hepatic LEPR, suggesting the development of resistance against leptin anti-lipogenic actions. 12,13 Consequently, sustained abnormal hepatic lipid metabolism provokes extensive oxidative stress 14,15 and chronic inflammation 16,17 followed by tissue damage, apoptosis, and progressive declines in liver functions. 3,18 Currently, the clinical management of MAFLD merely consists of lifestyle modification since there is no FDA-approved pharmacological therapy.…”
Section: Introductionmentioning
confidence: 99%
“…One of the obesity-associated hormones produced by the adipocytes is the adiponectin, whose serum levels are inversely related to body mass index (BMI) and insulin resistance [5]. Different experimental evidence showed that increased adiponectin expression is associated with raised insulin sensitivity [6,7]. The human adiponectin gene ( ADIPOQ ) consists of three exons, and it maps on chromosome 3q27, where genome-wide scans have revealed a locus susceptible for type 2 diabetes [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, CRISPR/Cas9 was used to delete the Prdm14 and Otx2 genes from a mouse model. CRISPR/Cas9 cut genomic DNA homozygosity [19, 21], as did the normal gene targeting methods [8]. However, homologous recombination via CRISPR/Cas9 was more efficient than that achieved using normal gene targeting methods [10].…”
Section: Discussionmentioning
confidence: 99%
“…After weaning, two to three mice were kept in an open cage. The animal room was maintained at 24 ± 2°C with 55 ± 10% relative humidity and 12 h of artificial lighting from 08:00 to 20:00 and was kept under specific pathogen-free conditions, which were the same as in a previous study [8]. The glucose tolerance test was performed when mice were 6 weeks of age.…”
Section: Methodsmentioning
confidence: 99%